P-B11 Retreatment of HCV GT-1 in patients who failed previous short course combination DAA therapy with 12 weeks of LDV/SOF is highly effective. (January 2016) - Wilson, Eleanor; Kattakuzhy, Sarah; Tang, Lydia; Sims, Zayani; Mclaughlin, Mary; Price, Angie; Mo, Hongmei; Osinusi, Anu; Masur, Henry; Kohli, Anita
Abstract : Introduction: Directly-acting antivirals (DAAs) revolutionized HCV therapy, but retreatment options for patients failing combination DAA therapy remain unstudied. Our aim is to determine if HCV genotype-1 patients who failed short course therapy with 3 or 4 DAAs, including LDV/SOF, can be retreated with 12 weeks of LDV/SOF. Methods: In this single- center, open-label, phase 2a trial, patients with HCV gt-1, early stage (F0-F2) liver fibrosis and previous exposure to combination DAA therapy (LDV/SOF with GS-9451 ± GS-9669) were eligible for treatment with 12 weeks of LDV/SOF. HCV RNA was measured by the Abbott assay, lower level of quantitation (LLOQ) 12 IU/mL. The primary endpoint was HCV viral load (VL) less than LLOQ 12 weeks after end of therapy (SVR12). Deep sequencing of NS5B and NS5A regions was performed at baseline by Illumina next generation sequencing technology. Results: The study enrolled 34 persons; 32 (94%) completed 12 weeks of LDV/SOF. Two patients withdrew consent after Day 0. Participants were predominantly male (82%) and black (82%), mean age 58.9 years, and BMI 27.3 kg/m 2 . Baseline HCV VL was 1.3 × 106 IU/mL (IQR: 5.8 × 105 − 3.9 × 106), 76.5% (26/34) were infected with HCV gt 1a, and median Metavir fibrosis stage was 1. Time from relapse to retreatment was 22 weeks (±8 weeks). SVR12 rates were 91% (31/34; ITT). At baseline, 29/34 patients (85%) had resistance-associated variants (RAVs) consistent with greater than 25 fold resistance in NS5A. Of all patients completing therapy, 1 patient with NS5A RAVs relapsed. Conclusions: For the first time, we demonstrate a high SVR rate following retreatment with DAAs in patients who have previously failed DAA-only therapy.